Factors influencing length of stay in the Emergency Department in a Private Hospital in North Jakarta - Juss, Irwan (Universa Medicina, 2008)
Length of stay (LOS) is a key measure of Emergency Department (ED) throughput and a marker of quality objectives. Time studies that assess ED services may help to clarify the causes of prolonged ED service to patients. The objective of this study was to analyse factors influencing LOS in the ED of Private Hospital X. This study was conducted at the ED of Private Hospital X in North Jakarta. One hundred and seventy one adult patients were admitted via the over a period of three weeks in March 2008. Data recorded included characteristics of patients, service time of nurses, service time of physicians, and overall ED LOS. Anova and independent t-test were performed to determine factors associated with ED LOS. Elderly patients, patients in emergency status, patients with letters of referral, electrocardiogram (ECG) training for physicians and advance cardiac life support (ACLS) training for nurses were significantly associated with duration of service in the ED. Mean ED LOS was 50 Â± 20.7 minutes. Patient category and characteristics of physicians and nurses are important independent variables that influence the EDâs duration of service. Future research is necessary to determine how these and other factors can be incorporated into a model for predicting ED LOS.